FISTULA ARTERIOVENOSUS FASIALIS PADA KEHAMILAN - Risky Ilona Saputra,* Kumara Tini* (NEURONA, 2018)
FISTULA AVF OF SUPERFICIAL TEMPORAL ARTERY IS RARELY FOUND WE REPORT A CASE OF 34 YEARS OLD WOMEN WITH FACIAL AVF DURING HER THIRD PREGNANCY THE PATIENT WAS ADMITTED TO THE HOSPITAL WITH COMPLAIN OF PULSATING HEADACHE TINNITUS AND PULSATING MASS ON THE LEFT PREAURICULAR REGION